WEAR ANALYSIS OF VERTICAL COAL MILL PLATE - Bertawan Bertawan; Diah Kusuma Pratiwi (Indonesian Journal of Engineering and Science, 2022)
Vertical Coal Mill (VCM) is equipment for grinding and pulverizing coal into micron size. Rotary kilns then use the powders as fuel burners. The VCM has a housing section equipped with a lining plate as a wear and tear protector. The housing comprises segments with similar thicknesses and materials that are severe to wear due to gas-carrying solid particles hitting the surface. The specific material resilient to abrasion is required to extend operating services. This study aims to determine the wear properties of Hardlite and Everhard C500LE on the lining plate. Characterization of the samples, including composition, microstructure, hardness, and wear test. Microstructure observation shows that the more extensive and profound the wear marks formed, the higher the volume of exfoliated material. The test results show that the Fe-Cr-C hard-facing alloy significantly affects the hardness value of a material and its wear resistance. The hardness test results showed an average Hardlite overlay layer hardness value of 703 BHN (N/mm2), almost double that of Everhard C500LE.